Integrating Microbial Fuel Cells (MFCs) into the treatment of sulphate-rich wastewater - Couperthwaite, Jennifer (Centre for Bioprocess Engineering Research, 2016)
The use of laboratory scale Microbial Fuel Cells (MFCs) for the combined generation of electricity and the treatment of wastewater has been well documented in literature. In addition to this the integration of MFCs into wastewater treatment reactors has also been shown to have several benefits. These include the improved treatment of wastewater, reduced solid waste and the potential to offset the energy costs of the process through the generation of electricity (Du et al., 2007). The treatment of sulphate-rich wastewater, and in particular Acid Rock Drainage (ARD), has become of increasing importance in water sparse countries like South Africa where mining is currently and has taken place. A semi-passive method of continuous ARD waste treatment is currently being investigated within the Centre for Bioprocess Engineering Research (CeBER) (van Hille et al., 2015). This research involves the use of a Linear Flow Channel Reactor (LFCR) designed for combined biological sulphide reduction and sulphide oxidation to yield a sulphur product. Sulphate Reducing Bacteria (SRB) mediate the biological sulphide reduction. Chemical and biological sulphide oxidation takes place in a Floating Sulphur Biofilm (FSB) on the surface of the reactor and is mediated by Sulphide Oxidising Bacteria (SOB). Sulphate-rich wastewater can therefore be remediated through total sulphur species removal.